The comet assay for the evaluation of gut content genotoxicity: Use in human studies as an early biomarker of colon cancer risk - Ristori, Sara; Scavone, Francesca; Bartolozzi, Chiara; Giovannelli, Lisa (Mutation research. Genetic toxicology and environmental mutagenesis, 2022)
This short narrative review describes the use of the comet assay to evaluate the formation of genotoxic compounds in the gut lumen in human studies. The fecal water genotoxicity assay is based on ability of the gut content to induce genotoxicity in a cellular model, employing the aqueous component of the feces (fecal water) as this is supposed to contain most of the reactive species and to convey them to the intestinal epithelium. This non-invasive and low-cost assay has been demonstrated to be associated with colon cancer risk in animal models, and although the final validation against human tumors is lacking, it is widely used as a colo-rectal cancer risk biomarker in human nutritional intervention studies. The contribution given to the field of nutrition and cancer by the FW genotoxicity assay is highlighted, particularly in conjunction with other risk biomarkers, to shed light on the complex relationship among diet, microbiota, individual subject characteristics and the formation of genotoxic compounds in the gut. •Biomarkers for colo-rectal cancer risk are used in nutritional intervention studies.•Fecal water genotoxicity assay is one of the widely used early biomarkers.•Variability among laboratories makes it difficult to compare different data sets.•The measurement of DNA oxidative damage can improve method’s sensitivity.•Testing an array of biomarkers can provide useful information for prevention.